The Consequences of a Grabbing Hand: Five Selected Ways in Which Corruption Affects the Economy - Urbina, Dante A. (2020)
This article provides a survey of the existing literature on the effects of corruption on economic growth, foreign direct investment, income inequality, human development, and natural resources sector. Both the theoretical arguments and the empirical evidence are considered. It is found that: i) Several studies support a negative impact of corruption on growth (sand the wheel hypothesis), but there are also studies supporting a positive impact (grease the wheels hypothesis); ii) Concerning the impact of corruption on foreign direct investment, the evidence is also mixed since there are studies supporting a negative effect (the “grabbing hand” view), a positive effect (the “helping hand” view), and even no significant effect; iii) The great majority of studies find that corruption generates more income inequality, although some studies find an inverse relationship in regions where the informal sector is large; iv) There is a strong consensus regarding that corruption hampers human development by affecting aspects like poverty, education and health; v) Most of studies show that there is a direct association between corruption and the natural resources sector, especially in the mining, oil and gas industries. In addition, research challenges of economics of corruption in aspects like the definition of corruption, multidisciplinary perspective, econometric specification, and data issues are discussed.